Características léxico-semánticas de las crónicas futbolísticas del Real Madrid en el diario Marca - López González, Antonio María (Studia Romanica Posnaniensia, 2019)
Within the sports language, the lexical level is composed of slang, specialized terminology and figurative lexicon. This work analyzes the lexical-semantic characteristics of the football language in a corpus of news chronicles of Real Madrid football matches, published on the web site marca.com. We focus on the fundamental lexicon of these chronicles, as well as on the core concepts of them, their designations and the means of meaning.